Genetic Basis of Antimicrobial Resistant Gram-Negative Bacteria Isolated From Bloodstream in Brazil - Silveira, Melise Chaves; Rocha-de-Souza, Cláudio Marcos; de Oliveira Santos, Ivson Cassiano; Pontes, Leilane da Silva; Oliveira, Thamirys Rachel Tavares e; Tavares-Teixeira, Camila Bastos; Cossatis, Nataly de Almeida; Pereira, Natacha Ferreira; da Conceição-Neto, Orlando Carlos; da Costa, Bianca Santos; Rodrigues, Daiana Cristina Silva; Albano, Rodolpho Mattos; et al. (Frontiers in Medicine, 2021)
Multidrug-resistant microorganisms are a well-known global problem, and gram-negative bacilli are top-ranking. When these pathogens are associated with bloodstream infections (BSI), outcomes become even worse. Here we applied whole-genome sequencing to access information about clonal distribution, resistance mechanism diversity and other molecular aspects of gram-negative bacilli (GNB) isolated from bloodstream infections. It was possible to highlight international high-risk clones circulating in the Brazilian territory, such as CC258 for Klebsiella pneumoniae, ST79 for Acinetobacter baumannii and ST233 for Pseudomonas aeruginosa. Important associations can be made such as a negative correlation between CRISPR-Cas and K. pneumoniae CC258, while the genes blaTEM, blaKPC and blaCTX-M are highly associated with this clone. Specific relationships between A. baumannii clones and blaoxa-51 variants were also observed. All ST233 isolates showed the genes blaVIM and blaOXA486. In addition, some trends could be identified, where a new P. aeruginosa MDR clone (ST3079) , a novel A. baumannii clonal profile circulating in Brazil (ST848), and important resistance associations in the form of blaVIM-2 and blaIMP-56 being found together in one ST233 strain, stand out. Such findings may help to develop approaches to deal with BSI and even other nosocomial infections caused by these important GNB.